Blood and cloacal swab sampling for avian influenza monitoring has no effect on survival rates of free‐ranging ducks. (27th June 2015) - Guillemain, Matthieu; Champagnon, Jocelyn; Gourlay‐Larour, Marie‐Lucile; Cavallo, Francois; Brochet, Anne‐Laure; Hars, Jean; Massez, Gregoire; George, Thierry; Perroi, Pierre‐Yves; Jestin, Veronique; Caizergues, Alain; Clark, Robert
<x xml:space="preserve">Abstract</x> Concerns about the spread of avian influenza viruses (AIVs) have led to cloacal swab sampling of hundreds of thousands of birds worldwide as part of AIV surveillance schemes, but the effects of cloacal swabbing have not been adequately evaluated. We tested for differences between swabbed, swabbed and bled, and non‐sampled wild ducks in terms of live re‐encounter and dead recoveries for Common Pochard Aythya ferina and Tufted Duck Aythya fuligula, and also determined re‐encounter and recovery rates for Mallard Anas platyrhynchos and Common Teal Anas crecca. No effects of sampling methods were detected, except in Teal. Re‐encounter rates were lower in sampled Teal than in controls, with annual re‐encounter probabilities being 25% and 35% lower in males and females, respectively. Teal possibly left or avoided sampling sites, or sought sites where they were less detectable after sampling. In general, no deleterious effects were found, suggesting that cloacal swabbing and blood sampling are suitable methods for conducting AIV surveillance in ducks.